Auditory processing neurons influence song evaluation and strength of mate preference in female songbirds - Lawley, Koedi S.; Fenn, Thomas; Person, Emily; Huber, Holly; Zaharas, Kristina; Smith, Perry; Coulter, Austin; Prather, Jonathan F. (Frontiers in Neural Circuits, 2022)
Animals use a variety of complex signaling mechanisms to convey an array of information that can be detected by conspecifics and heterospecifics. Receivers of those signals perceive that information and use it to direct their subsequent actions. Thus, communication such as that which occurs between senders and receivers of vocal communication signals can be a powerful model in which to investigate the neural basis of sensory perception and action initiation that underlie decision making. In this study, we investigated how female songbirds perceive the quality of acoustic signals (songs) performed by males and use that information to express preference for one song among many possible alternatives. We use behavioral measurement of song preference before and after lesion-induced alteration of activity in an auditory processing area (caudal nidopallium, NC) for which we have previously described its interconnections with other auditory areas and downstream reward pathways. Our findings reveal that inactivating NC does not change a female’s ability or willingness to perform behavioral indicators of mate choice, nor does it change their ability to identify the songs of individual males. However, lesioning NC does induce a decrease in the strength of song preference for specific males more than others. That decrease does not result in a complete elimination of preference, as female preferences for specific males are still evident but not as strongly expressed after lesioning of NC. Taken together, these data indicate that NC plays a role in a female’s strength of preference in song evaluation and mate choice, and activity in NC is an important facet of mate choice.